Contact, Collaboration, and Conflict: Signal Integration of Syk-Coupled C-Type Lectin Receptors - Ostrop, Jenny; Lang, Roland (Journal of Immunology, 2017)
Several spleen tyrosine kinase-coupled C-type lectin receptors (CLRs) have emerged as important pattern recognition receptors for infectious danger. Because encounter with microbial pathogens leads to the simultaneous ligation of several CLRs and TLRs, the signals emanating from different pattern recognition receptors have to be integrated to achieve appropriate biological responses. In this review, we briefly summarize current knowledge about ligand recognition and core signaling by Syk-coupled CLRs. We then address mechanisms of synergistic and antagonistic crosstalk between different CLRs and with TLRs. Emerging evidence suggests that signal integration occurs through 1) direct interaction between receptors, 2) regulation of expression levels and localization, and 3) collaborative or conflicting signaling interference. Accordingly, we aim to provide a conceptual framework for the complex and sometimes unexpected outcome of CLR ligation in bacterial and fungal infection.
EVALuna2:7742